Immunomodulation Effects of Bryophyllum Pinnatum on Pregnant Pristane-Induced Lupus Mice Model - Nurdiana Nurdiana; Elvira Sari Dewi; Yuni Sari; Rahmawati Wahyuni; Aminah Maya; Nursari Abdul Syukur; Mirza Zaka Pratama; Wisnu Barlianto; Umi Kalsum; Kusworini Handono (Research Journal of Life Science, 2016)
Objective: To determine the effect of Bryophyllum pinnatum treatment in modulating immune response and the pregnancy outcomes of pregnant pristane-induced lupus mice model.Methods: Sixteen Balb/c mice were intraperitoneally injected with single 0.5 cc pristane to induce lupus manifestations. After 12 weeks of injection, mice were mated and considered as gestational day 0 (GD0). Mice were divided into 4 groups based on the dosages of Bryophyllum pinnatum: control (no treatment), B1 (10.5 mg/kg), B2 (21 mg/kg), and B3 (42 mg/kg). The treatment was given orally every day started from GD9 until 9 days. At the end of the study, blood pressure and fetal size were measured. Serum anti-dsDNA and urine albumin levels were measured by ELISA. Spleen T helper (Th) and mature B cells percentages were measured by flow cytometry.Results: Administration of Bryophyllum pinnatum reduced the percentages of Th1 (p=0.006), Th2 (p=0.005), Th17 (p=0.000), and mature B cells (p=0.007) in dose-dependent manner. B1 and B2 had significantly lower of systolic blood pressure compared to control (p=0.026 and p=0.022 respectively). Significantly lower of anti-dsDNA levels were found in B1 group compared to control (p=0.014). However, no significantly different of urine albumin levels were found between groups. Bryophyllum pinnatum also significantly increased the fetus body weight in dose-dependent manner (p=0.000).Conclusion: Treatment of Bryophyllum pinnatum could improve the pregnancy outcome and modulate the immune response in pregnant pristane-induced lupus mice. Therefore, Bryophyllum pinnatum is a potential herb which can be developed as an immunosuppressive agent in the future.